Effects of annealing temperature on the optical properties and device performance of Ag / n-Si / CuPc / Ag solar cell prepared via spin coating method - HanashriahHassan,; Noor Baa’yahIbrahim,; Zahari Ibarahim, (Universiti Kebangsaan Malaysia, 2010)
Copper phthalocyanine (CuPc) thin films have been prepared using a simple spin coating method. The films were annealed at 5 different temperatures (323, 373, 473, 523 and 573 K) for one hour in air. Optical properties study using the UV-Vis spectrophotometer showed that in the range of wavelength of 300-800 nm, all of the films have identical absorption coefficient patterns and there was no systematic changes with respect to annealing temperature. The film annealed at 373 K showed the highest absorbance while the lowest absorbance was shown by the film annealed at 323 K. The results showed that the optical band gaps depended on the temperature. The film annealed at 373 K has the lowest optical energy gap. Using the five annealed films, solar cell with the configuration of Ag / n-Si / CuPc / Ag were fabricated. Under the 50 W/cm2 light illumination, the current voltage measurements at room temperature were carried out on the device. The device which consists of film annealed at 373 K exhibited the best photovoltaic characteristics. The different annealing temperature also affect the photovoltaic behavior of the devices in a non-systematic way.